2017
DOI: 10.1186/s12879-017-2582-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial bloodstream infections in a tertiary infectious diseases hospital in Northern Vietnam: aetiology, drug resistance, and treatment outcome

Abstract: BackgroundBloodstream infections (BSIs) are associated with high morbidity and mortality worldwide. However their aetiology, antimicrobial susceptibilities and associated outcomes differ between developed and developing countries. Systematic data from Vietnam are scarce. Here we present aetiologic data on BSI in adults admitted to a large tertiary referral hospital for infectious diseases in Hanoi, Vietnam.MethodsA retrospective study was conducted at the National Hospital for Tropical Diseases between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 43 publications
4
48
2
2
Order By: Relevance
“…22,23 Similarly, Dat et al (2017) has documented 100% sensitivity to vancomycin and linezolid, as given in our study. 24 All these findings are equally in comparison with our study.…”
Section: Discussionsupporting
confidence: 88%
“…22,23 Similarly, Dat et al (2017) has documented 100% sensitivity to vancomycin and linezolid, as given in our study. 24 All these findings are equally in comparison with our study.…”
Section: Discussionsupporting
confidence: 88%
“…Data for Vietnam remain limited. 37% of staphylococci isolated from bloodstream infections in a tertiary infectious diseases hospital in North Vietnam have been reported as MRSA 10 . A similar proportion (40%) was found among isolates causing infective endocarditis in tertiary care hospitals of South Vietnam 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of representation for each GLASS organism may partly be a reflection of their respective burdens on healthcare. A study at a tertiary hospital in Hanoi showed that K. pneumoniae and E. coli were responsible for 17.5% and 17.3% of blood stream infections (BSI) respectively (Dat et al, 2017), and, in a paediatric setting in Cambodia, Salmonella spp. were shown to be responsible for 30.4% of BSI (Fox-Lewis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%